2018
DOI: 10.1021/acs.iecr.7b05395
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic, Mechanical, and Glasstomeric Properties of Precision Polyolefins Containing a Phenyl Branch at Every Five Carbons

Abstract: Mechanical and viscoelastic properties of precision polyolefins, poly­(4-phenylcyclopentene) (P4PCP) and its hydrogenated analog (H2-P4PCP) containing atactic phenyl branches at exactly every five carbons along the backbone are explored. Both materials are amorphous with a glass transition temperature of ∼17 ± 3 °C. Rheological investigations determined that P4PCP has an entanglement molar mass (M e = 10.0 kg mol–1) much higher and closer to polystyrene than H2-P4PCP (M e = 3.6 kg mol–1). Both materials have e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…P4PCP and H 2 –P4PCP are rubbery amorphous materials with a nearly identical T g (17 ± 2 °C) just below ambient temperature which is a key attribute for sound and vibration dampening materials . Further exploration of the viscoelastic and mechanical properties revealed that both share similar density (ρ 24°C = 1.03 ± 0.01 g cm –3 ), but P4PCP has a much higher entanglement molar mass ( M e = 10.0 kg mol –1 ) versus H 2 –P4PCP (3.6 kg mol –1 ) leading to differing mechanical properties at similar M n . H 2 –P4PCP, which can be likened to an ethylene–styrene (ES) copolymer with exactly 71.4% w/w styrene, is a model material for studying property differences between precise and imprecise microstructure.…”
Section: Challenges With Admetmentioning
confidence: 99%
See 1 more Smart Citation
“…P4PCP and H 2 –P4PCP are rubbery amorphous materials with a nearly identical T g (17 ± 2 °C) just below ambient temperature which is a key attribute for sound and vibration dampening materials . Further exploration of the viscoelastic and mechanical properties revealed that both share similar density (ρ 24°C = 1.03 ± 0.01 g cm –3 ), but P4PCP has a much higher entanglement molar mass ( M e = 10.0 kg mol –1 ) versus H 2 –P4PCP (3.6 kg mol –1 ) leading to differing mechanical properties at similar M n . H 2 –P4PCP, which can be likened to an ethylene–styrene (ES) copolymer with exactly 71.4% w/w styrene, is a model material for studying property differences between precise and imprecise microstructure.…”
Section: Challenges With Admetmentioning
confidence: 99%
“…Statistical ES copolymers previously reported display higher values, which vary greatly with only a 4% difference in composition. Values are from ref .…”
Section: Challenges With Admetmentioning
confidence: 99%
“…We note that due to the odd integer branch topology, an alternative descriptor is a perfectly alternating trimethylene‐styrene copolymer. This material, which we term here as p 5Ph, has a reduced T g (17 ± 2 °C) and entanglement molar mass ( M e ) of 3.6 kg mol −1 when compared to PS (13 kg mol −1 ) due to the trimethylene segment . In a recent study, we reported interesting “glasstomeric” behavior of p 5Ph, which has an elongation at break >1000% and has an elastic recovery of ≈95% from 500% strain at a rate of 0.02 s −1 .…”
Section: Introductionmentioning
confidence: 98%
“…This material, which we term here as p 5Ph, has a reduced T g (17 ± 2 °C) and entanglement molar mass ( M e ) of 3.6 kg mol −1 when compared to PS (13 kg mol −1 ) due to the trimethylene segment . In a recent study, we reported interesting “glasstomeric” behavior of p 5Ph, which has an elongation at break >1000% and has an elastic recovery of ≈95% from 500% strain at a rate of 0.02 s −1 . Given the markedly different properties between PS and p 5Ph, we rationalized that sulfonation of p 5Ph could potentially lead to an analog of PSS with advantageous properties and the potential ability to be thermally processed.…”
Section: Introductionmentioning
confidence: 98%
“…The parent poly(4-phenylcyclopentene) (P4PCP) and its hydrogenated analog (p5Ph) are both amorphous, have a low glass transition temperature (T g ≈ 17 °C), and are well entangled at the degree of polymerization (~712) used in this study. [13][14][15][16] We recently investigated p5PhSA neutralized with a variety of metal cations, and found that in the dry state the ions and sulfonate groups strongly nanophase separate from the polymer backbone and self-assemble into percolated ionic aggregates. 17 We thus anticipated that p5PhSA would also nanophase separate into hydrophilic and hydrophobic domains.…”
Section: Introductionmentioning
confidence: 99%